Ru-SATED scale and Sleep Health Index: A systematic review of two leading multidimensional sleep health measures and frameworks across the globe - Meng, Runtang; BaHammam, Ahmed S.; Dzierzewski, Joseph M.; Yang, Nongnong; Vézina-Im, Lydi-Anne; Ying Lau, Esther Yuet; Sun, Iris Rongwei; Gregory, Alice M.; Zeitzer, Jamie M.; Quan, Stuart F.; Dietch, Jessica R.; Szklo-Coxe, Mariana; et al. (Sleep Medicine Reviews, 2026)
Research using the multidimensional sleep health (MDSH) framework has increased globally, often relying on self-report measures. The Ru-SATED scale and Sleep Health Index (SHI) are common self-report measures of MDSH, but comparative data on their measurement properties and contextual characteristics remain limited. Seven electronic databases were searched for measurement properties and uses of the two scales over the past twelve years. This review identified 19 psychometric validation studies concerning two original and 17 cross-cultural, and summarized contextual comparison of MDSH measures and frameworks. Measurement properties of both measures were assessed with the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guideline, and contextual comparisons were conducted narratively. Both measures exhibited acceptable psychometric properties across diverse cultural settings, with the SHI findings showing greater consistency than those of the Ru-SATED scale. Aggregating the Ru-SATED and SHI frameworks fully covered the sleep characteristics assessed by five instruments grounded in the World Sleep Society initiative, encompassing regularity, satisfaction, alertness, timing, efficiency, duration, and disorder. Notably, the SHI framework incorporates targeted sleep disorder assessment while the Ru-SATED framework specifically excludes such assessment, highlighting the distinct focus and scope of each tool. Instrument selection depends primarily on research purpose, study sample, and intended use. We recommend characterizing both sleep health and sleep disorders to fully capture the complex relationships between sleep and health outcomes.
Keywords: COSMIN; MDSH frameworks; Multidimensional sleep health; Ru-SATED scale; Sleep Health Index